Upper anterior zone restoration with composites - Lamas Lara, César (2009)
The anterior sector problems are very common in our professional practice and became vital importance to make a suitable rehabilitation in these cases; we can not do a good rehabilitation if we do not know the basic characteristics, both aesthetic and functional. Today the composites are a valid alternative for the restoration of the anterior sector, since they offer to us a conservative and aesthetic possibility, but independently of the material to use we have to based on certain rules or parameters to realize a suitable rehabilitation. In this article the basic criteria to keep in mind are detailed to restore the anterior sector as well as the skills on having used composites.